1998
DOI: 10.1021/om980279g
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Regioselectivity of Alkene Hydrosilylation Catalyzed by Organolanthanide and Group 3 Metallocene Complexes

Abstract: The regioselectivity of monosubstituted alkene hydrosilylation catalyzed by organolanthanide and group 3 organometallic complexes has been studied as a function of catalyst structure. A wide variety of catalyst variations were shown to be compatible with the hydrosilylation process. Several novel complexes were synthesized to widen the scope of this investigation. The results show complexes containing larger lanthanide metal ions and reduced substitution on the cyclopentadienyl ligands produce increased yields… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
34
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(37 citation statements)
references
References 45 publications
(26 reference statements)
3
34
0
Order By: Relevance
“…This observation is in accordance with the results obtained by Molander et al in their study of the influence of parameters such as metal radius and ligand sterics on the regioselectivity of 1-decene hydrosilylation by rare-earth metallocenes [7]. They showed that a major condition for the increase in 2,1-regioisomer vs. 1,2-regioisomer was the accessible space at the active site of the catalyst and that the combination of a small metal with a sterically hindered ligand gave complete 1,2-regioselectivity.…”
Section: Regioselectivitysupporting
confidence: 93%
See 1 more Smart Citation
“…This observation is in accordance with the results obtained by Molander et al in their study of the influence of parameters such as metal radius and ligand sterics on the regioselectivity of 1-decene hydrosilylation by rare-earth metallocenes [7]. They showed that a major condition for the increase in 2,1-regioisomer vs. 1,2-regioisomer was the accessible space at the active site of the catalyst and that the combination of a small metal with a sterically hindered ligand gave complete 1,2-regioselectivity.…”
Section: Regioselectivitysupporting
confidence: 93%
“…Length of the link. According to the previous studies performed on rare-earth metallocenes in comparison with rare-earth ansa-metallocenes, the presence of a link between the two cyclopentadienyl-moieties has been shown to influence the reactivity and the regioselectivity of the corresponding catalysts significantly by creating a well defined space around the active site [7]. In the case of ''constrained geometry'' catalysts, the length of the link …”
Section: -Decenementioning
confidence: 99%
“…The organometallic chemistry of trivalent rare earth complexes has found many important applications in the field of catalysis, including the metal-catalyzed hydrophosphonylation of carbonyls, 1 hydrogenation, [2][3][4][5][6][7] the catalytic addition of H-X to unsaturated moieties (e.g. hydroamination, 8-16 hydrosilylation, 10,[16][17][18][19][20] hydrophosphination, [21][22][23][24] hydroboration, 25,26 and hydroalkoxylation [27][28][29][30] ), and especially polymerization chemistry. [31][32][33][34][35][36][37][38][39][40][41][42][43][44] However, compared to research on organotransition-metal species, the study of rare earth complexes remains much less explored.…”
Section: Introductionmentioning
confidence: 99%
“…Asymmetric hydrosilylation of α -substituted styrenes ( 31 ) with phenylsilane by a chiral organolanthanide catalyst ( 32 ) gave the corresponding benzylic tert -alkylsilanes ( 33 ) in high enantiomeric excess (Scheme 9.7 ) [22] . …”
Section: Asymmetric Hydrosilylation Of Styrene and Its Derivativesmentioning
confidence: 99%